2019
DOI: 10.1016/j.chemosphere.2018.09.116
|View full text |Cite
|
Sign up to set email alerts
|

The complexation of steroid hormones into cyclodextrin alters the toxic effects on the biological parameters of zebrafish (Danio rerio)

Abstract: The objective of this study was to evaluate the toxic effects of progesterone (PF) and estradiol (EF) and the effect of these steroid hormones complexed into cyclodextrins, commercially available drugs, such as micronized progesterone (PM) and transdermal estradiol (ET), and evaluate them as endocrine disruptors through biological parameters of Danio rerio. An acute toxicity test was performed with hormones using D. rerio embryos according to OECD 236 guidelines. The heart rate, mortality, and teratogenic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Higher frequencies of congenital malformations were reported in 18 animal studies, including 6 studies evaluating any congenital malformation (Andrew and Staples 1977;Eibs et al 1982;Prahalada et al 1985a;Prahalada et al 1985b;Sannes et al 1983;Silva et al 2019) and 12 studies measuring specific congenital malformations (Dohler et al 1986;Foote et al 1968;Forsberg and Jacobsohn 1969;Forsberg et al 1968;Graf and Neumann 1972;Iqbal et al 2012;Johnstone and Franklin 1964;Pamir et al 2006;Vega Matuszczyk and Larsson 1995;Ward 1972;Whalen et al 1966;Wharton and Scott 1964). Of note, the animal studies reporting higher rates of congenital malformations included the 10, predominantly older, studies that were descriptive in nature and did not conduct statistical analyses [see Malformations-Animal, Filter -Effect Significance in Tableau (NTP 2020)].…”
Section: Figure 5 Number Of Studies Evaluating the Association Betwementioning
confidence: 88%
See 2 more Smart Citations
“…Higher frequencies of congenital malformations were reported in 18 animal studies, including 6 studies evaluating any congenital malformation (Andrew and Staples 1977;Eibs et al 1982;Prahalada et al 1985a;Prahalada et al 1985b;Sannes et al 1983;Silva et al 2019) and 12 studies measuring specific congenital malformations (Dohler et al 1986;Foote et al 1968;Forsberg and Jacobsohn 1969;Forsberg et al 1968;Graf and Neumann 1972;Iqbal et al 2012;Johnstone and Franklin 1964;Pamir et al 2006;Vega Matuszczyk and Larsson 1995;Ward 1972;Whalen et al 1966;Wharton and Scott 1964). Of note, the animal studies reporting higher rates of congenital malformations included the 10, predominantly older, studies that were descriptive in nature and did not conduct statistical analyses [see Malformations-Animal, Filter -Effect Significance in Tableau (NTP 2020)].…”
Section: Figure 5 Number Of Studies Evaluating the Association Betwementioning
confidence: 88%
“…First-trimester exposure to 17OHPC has been hypothesized to be without elevated risk for congenital malformations (Dudas et al 2006;Hilgers et al 2015) and might be a candidate for a future systematic review to evaluate a lack of effect. Progesterone exposure did not result in higher rates of congenital malformation in humans (four studies) and nonhuman mammalian animal models (five studies), but was reported to induce spinal and tail malformations in embryonic zebrafish (Silva et al 2019) and neural tube defects when administered to chick embryos at reportedly supranormal levels (Iqbal et al 2012;Pamir et al 2006). Progesterone is regularly administered in the first trimester to aid in the maintenance of pregnancy in women undergoing infertility treatment and is generally accepted to have no risk of congenital malformations (Hilgers et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zebrafish model was already used for studies on the effect of caffeine on, e.g., behavior [18] and development [19]. Although some studies demonstrated the attenuation of biological functions in zebrafish by some CDs (for example [20] and [21]) we are the first to report increased toxicity of caffeine when complexed with CDs.…”
Section: Figurementioning
confidence: 95%
“…The eggs were collected, rinsed in water, and transferred 489 to Petry dishes and for determination of the overall egg number and viability (i.e. fertilized) (Silva et al, 2019;Lammer et al, 2009).…”
Section: Egg Productionmentioning
confidence: 99%